Calorie Restriction, Stem Cells, and Rejuvenation Approach - Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2016)
Aging may be defined as the time-dependent deterioration in function of an organism associated with or responsible for the increase in susceptibility to disease and probability of death with advancing age (Harman, 1981; Cefalu, 2011). Generally, the aging organisms are characterized by both biochemical and functional declines. Declining of basal metabolism rates, protein turnover, glucose tolerance, reproductive capacity, telomere shortening, and oxidative phosphorylation are related to the biochemical. Whilst, lung expansion volume, renal glomerular and tubular capacities, cardiovascular performance, musculoskeletal system, nerve conduction velocity, endocrine and exocrine systems, immunological defenses, and sensory systems are associated with the physiological declining (Baynes and Dominiczak, 2015). Some evidences indicated that, although members of a species develop into adults in the same way, even genetically similar or identical individuals, raised in identical conditions and eating identical food, but they may age differently (Baynes and Dominiczak, 2015). These aging differences are attributable to the life style particularly calorie and dietary restriction intakes, reactive oxygen species (ROS) production, and thus its implication on severity of damage, repair capacity, and error accumulation in cellular genetic material (Baynes and Dominiczak, 2015; Mihaylova et al., 2014; Mazzoccoli et al., 2014). Therefore, in molecular terms, aging can be defined as a decline of the homeostatic mechanisms that ensure the function of cells, tissues, and organs systems (Mazzoccoli et al., 2014). Accordingly, if the homeostatic mechanism can be repaired, the result is rejuvenation.